Does oil corrupt? Evidence from a multivariate VAR in Iran - Mohammad Reza Farzanegan; Reza Zamani (Philipps-University Marburg, School of Business and Economics, 2023)
We examine the response of the news-based Corruption Reflection Index (CRI) to positive shocks in oil revenues in Iran. Using annual data from 1962 to 2019, we employ the Vector Autoregressive (VAR) model and analyze impulse response functions. Our findings reveal a positive and significant response of corruption to oil shocks. The key channels through which this relationship operates include inflation, military spending, and the degradation of democratic institutions. Moreover, we provide a case study of clientelism in public investment projects in Iran from 2002 to 2012 and their impact on the public budget.
Keywords: 330; Corruption; Oil rents; Resource curse; Conflict; Iran; VAR model